Primeira e segunda geração de jovens imigrantes argentinos, bolivianos e peruanos em São Paulo: um estudo psicossocial da identidade e aculturação - Huayhua, Gladys Llajaruna (2007)
The purpose o this study analyzed the Social Psychology study of the identity and the process of acculturation of the young Argentine, Bolivian and Peruvian immigrants of first and second generation that lives in São Paulo. The young had been considered that had between 17 the 30 years of age, and that they live in this country it has at least two years. The study it was based on the theory of acculturation strategies and the intercultural psychology of Berry, in the same way to the theory of group and the preconception of Tajfel, reflections of Martin-Baró, and the development of the identity according to Antonio Ciampa, as well as of other authors. It was used descriptive quantitative methodology of the scale of acculturation and the questionnaire of general information. For the collection of data in them we base on these two instruments, the scale of acculturation of the model of Berry and the questionnaire of general information of immigrants in Brazil, of Bolivian and Peruvian Tito Valencia who had been appropriate for the researcher for the population of young of Argentine immigrant, that lives in Brazil. This study in it allowed them to know as if they mobilize these immigrants in the Brazilian society, as well as the strategies that use to insert to this country in the same way the adaptation. The sixty young is integrated to the Brazilian society, however they present you differentiate in the uses of the strategies in the daily activities of its routine in Brazil. These strategies go to depend on the previous factors and during the process of acculturation to the Brazilian society, in equal way of as the Brazilians receive to the Latin American immigrants. This process showed the movement that all immigrant passes of descontrução and reconstruction of the cultural identity